SIFAT-SIFAT PREBIOTIK RIPE BANANA CHIP (RBC) Musa sinensis - Nurhayati Nurhayati; Tamtarini Tamtarini; Jayus Jayus; Eka Ruriani; Leni Nurul Hidayati (JURNAL AGROTEKNOLOGI, 2014)
Ripe banana chip (RBC) Musa sinensis is one type of ripe banana chip that can be processed by using the vacuum frying technology combined with freezing process. This technology could affect the prebiotic properties of the RBC product. Therefore, this research aims to evaluate the prebiotic properties of ripe banana chip (RBC). Insoluble indigestible fraction (IIF) was isolated from RBC by enzymatic method. using. The prebiotic properties of IIF were based on their ability to increase probiotic population and decrease enterobactericeae (Eschericia coli and Salmonella sp.) population in the volunteers fecal, profile of short chain fatty acids (SCFA) and the value of prebiotic index (IP). The results showed that Frozen vacuum-RBC and vacuum-RBC were able to increase the probiotic growth about 1-2 log of the bacterial population, but unable to decrease enterobactericeae population. Vacuum-RBC was higher to produce butyric acid (3.46 mM) than frozen vacum-RBC and higher of IP (0.39) than RBC frozen vacuum (0.04). It can be concluded that vacuum-RBC have better prebiotic properties than frozen vacuum-RBC.Keywords: ripe banana chip (RBC), vacuum frying, freezing, short chain fattry acid, prebiotic index